2006
DOI: 10.1111/j.1538-7836.2006.02239.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function in patients with acute coronary syndrome (ACS) predicts recurrent ACS

Abstract: See also Boos CJ, Lip GYH. Platelet activation and cardiovascular outcomes in acute coronary syndromes. This issue, pp 2542-3. Harrison P, Keeling D. Platelet hyperactivity and risk of recurrent thrombosis. This issue, pp 2544-6. Summary. Background: Platelet hyperfunction contributes to acute coronary syndromes (ACS). Thus, we hypothesized that platelet function under high shear stress predicts recurrent ACS during long-term follow-up of ACS patients. Patients and methods: Consecutive ACS patients (n ¼ 208) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 27 publications
4
88
1
Order By: Relevance
“…Moreover, Gianetti and colleagues demonstrated an independent positive relation of aspirin resistance, estimated by the PFA-100, and 6-mo clinical recurrence of symptoms in 175 patients with stable or unstable coronary artery disease who underwent successful coronary stenting. 6 Another report by Fuchs et al, 7 with a study population of 208 patients with unstable coronary artery disease, also yielded a significant independent association of aspirin resistance, assessed by PFA-100, and major atherothrombotic long-term events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Gianetti and colleagues demonstrated an independent positive relation of aspirin resistance, estimated by the PFA-100, and 6-mo clinical recurrence of symptoms in 175 patients with stable or unstable coronary artery disease who underwent successful coronary stenting. 6 Another report by Fuchs et al, 7 with a study population of 208 patients with unstable coronary artery disease, also yielded a significant independent association of aspirin resistance, assessed by PFA-100, and major atherothrombotic long-term events.…”
Section: Discussionmentioning
confidence: 99%
“…However, Fucsh et al, in a study of patients with ACS, have shown that inclusion of von Willebrand factor levels in a multivariate Cox regression model did not alter the predictive value of a low PFA-100 CEPI-CT for the incidence of long-term recurrent instability. 7 Third, patients with NSTE-ACS, and therefore probably with some degree of platelet hyperactivity, were included in this study. Subsequently, low values of PFA-100 in the study patients may reflect a transient phenomenon of the acute phase.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Eight studies were eliminated because they were not prospective studies, 4 because they reported only clopidogrel resistance, 2 because they did not evaluate clinical cardiovascular recurrences during the follow-up but only surrogate markers, and 1 because only a meeting abstract was available. As a result, a total of 11 prospective studies were included in the meta-analysis [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Search Resultsmentioning
confidence: 99%
“…Therefore, closure time, as determined on the PFA-100®, is strongly influenced by the amount of von Willebrand factor (vWF) [12]. Increased plasma vWF levels and a higher vWF-ristocetin cofactor activity have been related to shorter CT values on the PFA-100®, and these patients may be considered poor responders to ASA [13,14]. In our study, the agreement between the LTA and PFA-100® test results was poor, as only two patients were identified as non-responders using both methods (2.0%).…”
Section: Discussionmentioning
confidence: 99%